Marital Discord, Past Depression, and Metabolic Responses to High-Fat Meals: Interpersonal Pathways to Obesity - Kiecolt-Glaser, Janice K. (Psychoneuroendocrinology, 2014)
BACKGROUND: Longitudinal studies have implicated both marital distress and depression in the development of the metabolic syndrome, a risk factor for diabetes and cardiovascular disease. This study addressed the impact of hostile marital interactions and a mood disorder history on obesity-related metabolic responses to high-fat meals. METHODS: This double-blind, randomized crossover study included serial assessments of resting energy expenditure (REE), fat and carbohydrate oxidation, triglycerides, insulin, glucose, interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-α) before and after two high-fat meals. During two separate 9.5 hour visits, 43 healthy married couples, ages 24 to 61 (mean=38.22), received either a high saturated fat meal or a high oleic sunflower oil meal, both 930 kcal and 60 g fat. The Structured Diagnostic Interview for DSM-IV assessed mood disorder history. Couples discussed a marital disagreement during both visits; behavioral coding of these interactions provided data on hostile marital behaviors. RESULTS: Men and women who displayed more hostile behaviors and who also had a mood disorder history had significantly lower post-meal REE, higher insulin, and higher peak triglyceride responses than other participants, with nonsignificant effects for fat and carbohydrate oxidation. Participants with a mood disorder history had a steeper rise in postprandial IL-6 and glucose than those without a past history. Higher levels of hostile behaviors were associated with higher post-meal TNF-α. The two meals did not differ on any outcome assessed. CONCLUSIONS: People spend about 18 of every 24 hours in a postprandial state, and dining with one’s partner is a common daily event. Among subjects with a mood disorder history, the cumulative 6.75-hour difference between high and low hostile behaviors translates into 128 kcal, a difference that could add 7.6 pounds/year. Our findings illustrate novel pathways through which chronic marital stress and a mood disorder history synergistically heighten the risk for obesity, metabolic syndrome, and cardiovascular disease.